Predictors of satisfaction with the succession process in family firms - Sharma, Pramodita; Chrisman, James J.; Chua, Jess H. (Journal of Business Venturing, 2003)
Recent theoretical developments suggest that satisfaction with the succession process in family firms is enhanced by the incumbent's propensity to step aside, the successor's willingness to take over, agreement among family members to maintain family involvement in the business, acceptance of individual roles, and succession planning. Data from incumbent leaders and successors provide strong support for these relationships. Incumbents and successors disagree, however, about the importance of each other's role. This implies a need to align these strategic stakeholders' perceptions in the family firm. Our research methodology also highlights the importance of considering multiple stakeholder groups in conducting family firm research.